Pragmatism and classical American philosophy - edited by John J. Stuhr (Oxford University Press, 2000)
Pragmatism and Classical American Philosophy, now revised and expanded in this second edition, presents the essential writings of the major philosophers of this tradition: Charles S. Peirce, William James, Josiah Royce, George Santayana, John Dewey, and George Herbert Mead. Illuminating introductory essays, written especially for this volume by distinguished scholars of American philosophy, provide biographical and cultural context as well as original critical and interpretive perspectives. This edition also includes all new selections and interpretive essays that situate pragmatism and classical American philosophy in a wider American philosophical context, including: Ralph Waldo Emerson and transcendentalism; Jane Addams, feminism, and writings of American women; Borden Parker Bowne, personalism, and idealism; Alain Locke and Afro-American thought; and John Herman Randall, Jr., nationalism and realism. Up-to-date suggestions for further reading will benefit both introductory and advanced readers